Characteristics of fractionated drop-in liquid fuel of plastic wastes from a commercial pyrolysis plant. (1st May 2021) - Lee, Doyeon; Nam, Hoseok; Wang, Shuang; Kim, Hana; Kim, Jung Hwan; Won, Yooseob; Hwang, Byung Wook; Kim, Young Doo; Nam, Hyungseok; Lee, Kyong-Hwan; Ryu, Ho-Jung
Graphical abstract: Highlights: Comprehensive physical and chemical properties of plastic pyrolysis fuel studied. Relationship between boiling point and vapor temperature during separation was found. Best HHV was 44.6 MJ/kg with 3.6 cSt for viscosity and 12 mg/g for TAN. Above 40% of olefins included in lighter fractions (<300 °Cb.p. ). CO2 reduction potential for plastic pyrolysis was determined to be 0.26 tCO2 /ton. Abstract: Pyrolysis is a waste conversion technology to solve an increasing plastic waste issue worldwide. Waste plastic pyrolysis fuel from a commercial-scale pyrolysis plant (10 ton/day) was comprehensively investigated using distillation methods by separating the crude pyrolysis fuel to isolate the diesel-like pyrolysis fuel fraction (C9 –C25 for fraction 2 + fraction 3, middle distillate). Other fractions were C5 –C10 for the light distillate (fraction 1), and >C25 for the heavy distillate (fraction 4). The relationship between the fuel boiling point and liquid vapor temperature were found for designing a scaled-up oil separation process. The diesel grade pyrolysis fuel fraction comprised approximately 70–80% of the crude pyrolysis fuel, wherein it had values of 43–45 MJ/kg, 1–6 cSt, and 12–42 mgKOH /goil . Meanwhile, the elemental ratios of the crude pyrolysis oil improved to 0.1 for O/C and 1.9 for H/C after separation, close to petroleum fuels (0.0 O/C and 1.95 H/C). The highest relative chemical composition was the olefins (46% in fraction 1 and 41% in fraction 2), whereas the paraffin was approximately 15–20% in the light fraction. Finally, the potential CO2 reduction for the plastic waste-to-energy process was evaluated, revealing that a total of 0.26 tCO2 /tonwaste of emissions could be avoided during the waste plastic pyrolysis process.